An Empirical Investigation on Customer Perception towards Aviation Accidents AND its Effects - Dr.V. Suganya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research studies on various criteria which were used to evaluate public’s perception or point of view on different aviation crisis. It is concentrated on general public’s reaction to various crisis like Hijack, Bomb Threat, Sabotage etc. This research is to know psychological impacts on general public and the aftermaths of the crisis and their ways to overcome that traumatic phase. When an accident happens, the media usually exaggerates and it becomes crucial for an airline to rebuild the trust and loyalty amongst the people. This research also takes witnesses of the hijack into its account. It also provides insights on post-accident investigation and types of compensation provided by airlines to the victims. The research development used in this study was Descriptive Research Design. The sample size was 100 passengers. The sampling technique used to draw the sample was convenience sampling method. The tool used to collect the data from samples was questionnaires. The statistical analysis was done using SPSS software. Survey of trauma issues and more such things are observed from the victims.